Myocardial Injury in Multiple Myeloma Patients With Preserved Left Ventricular Ejection Fraction: Noninvasive Left Ventricular Pressure-Strain Myocardial Work - Liu, Zhiyue; Zhang, Li; Liu, Mei; Wang, Fang; Xiong, Yanqiu; Tang, Zhuoqin; Li, Qian; Lu, Qiuchen; Liang, Shichu; Niu, Ting; Huang, He (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Over one-half of multiple myeloma (MM) patients die of heart failure or arrhythmia. Left ventricular ejection fraction (LVEF) is used to describe left ventricular systolic function. However, depressed LVEF means advanced stage of left ventricular dysfunction in MM patients. Left ventricular pressure-strain-derived myocardial work (LVMW) is a novel and non-invasive method for evaluating left ventricular (LV) function related to LV dynamic pressure load. Myocardial work (MW) is assessed by LV myocardial work index (LVMWI), constructive work, wasted work and LV myocardial work efficiency (LVMWE). Herein, we aimed to investigate the value of LVMW in cardiac function assessment and clinical prognosis of MM patients with preserved LVEF. Methods: A total of 72 subjects, including 40 untreated MM patients with preserved ejection fraction (EF, including thick wall and normal wall groups) and 32 non-MM patients, were enrolled in this study. Laboratory data and clinical history of all patients were collected. All patients underwent comprehensive echocardiographic examinations, and then LVMWI and LVMWE were calculated. Moreover, cardiac adverse events (CAEs) were observed in MM patients treated with Bortezomib-based therapy after 6 months, and the prognostic value of MW was assessed. Results: (1) LV global myocardial work index (GWI), global myocardial work efficiency (GWE) and global longitudinal strain (GLS) were lower in the thick wall group of MM patients compared with the normal wall group and controls. Cardiac segmental analysis of LVMWI in MM patients showed apical sparing pattern. (2) The area under the curve (AUC) of GWE for judging the disease severity based on the Revised International Staging System (R-ISS) was 0.835 (95% CI: 0.684-0.933, P<0.05). (3) GWE, LgdFLC and arrhythmia were independent risk factors of CAEs. The AUC of GWE for predicting CAEs in MM patients treated with Bortezomib-based therapy for 6 months follow-up was 0.896 (95% CI: 0.758-0.970, P<0.05). Conclusions: MM patients with preserved EF had subclinical LV systolic dysfunction, which was worse in the thick wall group. LV myocardial work index presented as “apical sparing” in MM patients. A lower LV GWE may have a predictive value for CAEs in MM patients after 6 months of follow-up.